Gouzenko. The Untold Story - Sawatsky, John. (Toronto A Division of Cage Publishing Limited, 1984)
This book paints a picture of a complex and contradictory man. Igor Gouzenko came from an ultra-structured society where all decisions, from what job to take, to where to live, even what o eat, were made by the state. Suddenly, he wrenched himself and his family out of this structure into a new and foreign environment. And what waited for him in new society is described just in this unusual book.
Keywords: Biography